2004
DOI: 10.1128/iai.72.11.6650-6658.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4-Dependent Early Elicited Tumor Necrosis Factor Alpha Expression Is Critical for Innate Host Defense againstBordetella bronchiseptica

Abstract: Toll-like receptor 4 (TLR4) mediates the response to lipopolysaccharide, and its activation induces the expression of a large number of inflammatory genes, many of which are also induced by other pathogenassociated molecular patterns. Interestingly, the subset of genes that are dependent on TLR4 for optimal expression during gram-negative bacterial infection has not been determined. We have previously shown that TLR4-deficient mice rapidly develop acute pneumonia after inoculation with Bordetella bronchiseptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 40 publications
4
46
0
Order By: Relevance
“…These results are similar to those of Ramphal and colleagues (46) but differ somewhat from those of Faure et al (14), who reported inoculum-dependent impairments in bacterial clearance and survival after endobronchial instillation of the PA103 strain of P. aeruginosa. TLR4-deficient mice also have been shown to exhibit reduced resistance to pulmonary infection with other gram-negative bacteria, including Pasteurella pneumotropica (8), Haemophilus influenzae (65,66), Klebsiella pneumoniae (7,50), Bordetella bronchiseptica (38), and Acinetobacter baumanii (32), but not Legionella pneumophila (34), Francisella tularensis (9), or Escherichia coli (33). TLR2 had a subtler role than TLR4 in the host response to P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those of Ramphal and colleagues (46) but differ somewhat from those of Faure et al (14), who reported inoculum-dependent impairments in bacterial clearance and survival after endobronchial instillation of the PA103 strain of P. aeruginosa. TLR4-deficient mice also have been shown to exhibit reduced resistance to pulmonary infection with other gram-negative bacteria, including Pasteurella pneumotropica (8), Haemophilus influenzae (65,66), Klebsiella pneumoniae (7,50), Bordetella bronchiseptica (38), and Acinetobacter baumanii (32), but not Legionella pneumophila (34), Francisella tularensis (9), or Escherichia coli (33). TLR2 had a subtler role than TLR4 in the host response to P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo TNF-␣ neutralization experiments, Lps n and Lps d mice were i.p. injected 1 h before bacterial inoculation with 1 ml of PBS containing 1 mg of purified anti-mouse TNF-␣ from the MP6-XT3 mAb or with 1 mg of the rat IgG1 isotype control (eBioscience) (31). All experiments were performed in accordance with the guidelines of the French Agricultural Office and in compliance with the legislation governing animal studies.…”
Section: Animals and Infectionsmentioning
confidence: 99%
“…We have previously shown that one such receptor, TLR4, is critical for controlling the respiratory pathogen B. bronchiseptica (22). TLR4 d mice inoculated with a standard dose (5 ϫ 10 5 CFU in 50 l of PBS given by intranasal route) of B. bronchiseptica succumbed to bordetellosis as early as day 3 postinoculation, whereas TLR4 s mice survive and eventually clear bacteria from the lower respiratory tract (16).…”
Section: Tlr4 Is Required For Ab-mediated Clearance Of Bacteria From mentioning
confidence: 99%